BIOACTIVITY OF ENDOPHYTIC FUNGI EXTRACTS RESIDING IN THE ROOTS OF MISTLETOE (Dendrophthoe pentandra) - Oktiansyah, Rian; Habisukan, Ummi Hiras; Noviyanto, Noviyanto; Nasution, Sakinah Salman Ahmad; Febiantika, Imaniar; Octavia, Risky (BRIN Publishing (Penerbit BRIN), 2025)
Mistletoe (Dendrophthoe pentandra) is a parasitic plant that has traditional medicinal properties. This study examines the endophytic fungi found in mistletoe roots and their bioactivity. Endophytic fungal species are identified using their morphological traits. Potato Dextrose Broth (PDB) medium is utilized for both culture and extraction, with ethyl acetate as a solvent. The antioxidant test employed the DPPH method, whereas the antibacterial test used the paper disc diffusion method. Mistletoe roots yielded four endophytic fungus isolates (BR1–BR4). The findings of morphological study revealed that BR1 (Pythium sp.), BR2 (Trichoderma sp.), BR3 (Fusarium sp.), and BR4 (Mortierella sp.). The endophytic fungus BR4 (Mortierella sp.) had the highest potential antioxidant and antibacterial activities. This endophytic fungal extract has the potential to be a source of novel medications through additional investigation by isolating the pure component and in vivo studies.